1991
DOI: 10.1007/bf00011806
|View full text |Cite
|
Sign up to set email alerts
|

Endomycorrhizal fungal species mediate 15N transfer from soybean to maize in non-fumigated soil

Abstract: The effect of mycorrhizal inoculation on 15N transfer from soybean to maize was studied in fumigated and non-fumigated soil. Three Glomus species and a non-inoculated control were compared.In spite of higher levels of root colonization and more abundant hyphae associated with plants growing in fumigated soil, mycorrhizae-enhanced ~SN transfer to maize was significant only in non-fumigated plots. High 15N transfer was not only associated with high mycelium density in soil but also with low soil microbial carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…The presence of AMF could therefore intensify microbial competition, leading to smaller microbial populations in the rhizosphere. This hypothesis is supported by studies that showed that the presence of certain species of Glomus reduced the biomass of N-fixing microorganisms, a result of competition between root symbionts for C-containing plant exudates (16,36). In our study, however, the microbial populations in samples from the Spartina site were at least twice as large in terms of number and biomass as the microbial populations in samples from the Phragmites site, indicating that basic differences in plant growth and carbon allocation strategies are responsible for the observed differences in microbial populations.…”
Section: Discussionmentioning
confidence: 80%
“…The presence of AMF could therefore intensify microbial competition, leading to smaller microbial populations in the rhizosphere. This hypothesis is supported by studies that showed that the presence of certain species of Glomus reduced the biomass of N-fixing microorganisms, a result of competition between root symbionts for C-containing plant exudates (16,36). In our study, however, the microbial populations in samples from the Spartina site were at least twice as large in terms of number and biomass as the microbial populations in samples from the Phragmites site, indicating that basic differences in plant growth and carbon allocation strategies are responsible for the observed differences in microbial populations.…”
Section: Discussionmentioning
confidence: 80%
“…Reductions in root C exudation or changes in exudates composition induced by AMF activity could therefore intensify microbial competition leading to altered community structure and metabolic activity. This assumption is supported by studies that showed that the presence of certain species of Glomus reduced the biomass of nitrogen-fixing microorganisms, a result of competition for root exudates (Hamel et al 1991;Paul and Clark 1996). Changes in populations of functional groups such as nitrogenfixing bacteria could ultimately impact plant resource acquisition, plant nutrient status and performance.…”
Section: Introductionmentioning
confidence: 87%
“…Generally, results have shown that 15 N transfer can occur, although amounts have been relatively low. In addition, field experiments using soil fumigation and additions of mycorrhizal inoculum have indicated that 15 N transfer was enhanced by mycorrhizal presence and positively correlated with mycorrhizal hyphal density in the soil (Hamel et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Nitrogen-fixing donor plants were labeled with 15 N by solution application to leaves (Hogh-Jensen and Schjoerring, 2000), cut petioles (Martin et al, 1991b), or adventitious roots on stems (Hamel et al, 1991;Hamel and Smith, 1992) and grown with non-nodulating receiver plants. Generally, results have shown that 15 N transfer can occur, although amounts have been relatively low.…”
Section: Introductionmentioning
confidence: 99%